Business Process Reengineering for Inventory Module Manufacturing Company using Odoo V12.0 Application - Sudiyana, Kadek Alit; Sukarsa, I Made; Sunia Raharja, I Made (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 10 No 1 (2022): Vol. 10, No. 1, April 2022DO - 10.24843/JIM.2022.v10.i01.p02, 2021)
The use of Enterprise Resource Planning system in manufacturing companies aims to increase the companies’ productivity. In this case, a n integrated ERP system could maximize the companies’ production. Thus, the researcher conducted a study that discussed the application of ERP Odoo V12.0 system in a chicken company. This research focuse d on i nventory sectors . T here is no special system to manage the inventory section. The business proces s reengineering that has been done were the automatic purchase process, a special system or module to manage the inventory , the transfer of blast freezing process to manufacturing module, and the inventory reports. Based on the system testing by using User Acceptance Test that has been done , the researcher received quite good response s . In this case, t he scores obtained for the Inventory 1215 from 1760 (positive result ) . Keywords : Business Process Reengineering, Enterprise Resource Planning, Odoo V12.0, Inventory, User Acceptance Test